PENERAPAN METODE MIND MAPPING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA MATERI KAYANYA NEGERIKU DI KELAS IV MI HIDAYATUL MUBTADI’IN TASIKMADU MALANG - Muhaiminah Muhaiminah; Anwar Sa’dullah; Fita Mustafida (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2019)
AbstrakThis research is to find out the application of mind mapping methods that exist in MI Hidayatul Mubtadi'in Tasikmadu Malang to increase the learning motivation of material students like my country in class IV. This research was conducted by observation, interviews and documentation. In this study carried out by using classroom action research that did qualitative. Where the researcher conducted his own research as a fourth grade teacher at MI Hidayatul mubtadiin Tasikmadu. Starting from determining problems, arranging lesson plans, arranging learning activities, making collections of questions to determine the direction of learning activities using the mind mapping method. Learning mind mapping is a learning method by summarizing materials that need to be learned, then projecting ways to summarize, but in this case the teacher cannot implement it because the teacher does not understand the methods and media of learning. In this case, the researcher will discuss the mind mapping method to increase the learning motivation of the fourth grade students of MI Hidayatul Mubtadi in Tasikmadu Malang.Keyword : Motivation, Mind Mapping